Elastoplastic and contact analysis based on consistent dynamic formulation of co-rotational planar elements. (15th August 2017) - Cho, Haeseong; Joo, HyunShig; Shin, SangJoon; Kim, Haedong
Abstract: Co-rotational formulation is one of the approaches applicable to geometrically nonlinear problems in structural analysis. Based on the assumptions of small degree of strain and large displacement, the CR formulation allows an accurate geometrically nonlinear structural analysis. In this paper, an improved CR formulation for dynamic nonlinear analysis is developed for the planar element. Also, extension of the local formulation is conducted for an elastoplastic problem. A simplified approach for planar elastoplastic analyses is proposed by maintaining the original feature of the CR formulation. Moreover, a modified approach in the local formulation is suggested in order to improve the level of accuracy in the plastic state. Contact analysis using the Lagrange multiplier is then implemented. During the present validation procedure of the proposed approaches, four different planar elements are employed. Those elements are investigated with regard to efficiency and accuracy in a general geometrically nonlinear and a geometrically nonlinear/elastoplastic problem, respectively. It is found that the present dynamic formulations gives both accuracy and consistency for all types of the plane element. Also, comparison regarding the choice of the local formulation for the elastoplastic problem is systematically conducted and demonstrated.